Fondaparinux cross-reactivity in heparin-induced thrombocytopenia successfully treated with high-dose intravenous immunoglobulin and rivaroxaban. (2nd January 2020) - Manji, Farheen; Warkentin, Theodore E.; Sheppard, Jo-Ann I.; Lee, Adrienne
Abstract: HIT, a prothrombotic disorder caused by heparin-dependent antibodies, is often treated with fondaparinux, usually with good outcomes. A 70-year-old female developed severe HIT (platelet count, 25 × 10 9 /L) post-glioblastoma resection during heparin thromboprophylaxis, complicated by disseminated intravascular coagulation (DIC) and symptomatic lower-limb deep-vein thrombosis (DVT). Despite therapeutic-dose fondaparinux, thrombocytopenia/hypofibrinogenemia persisted, with new symptomatic catheter-associated upper-extremity DVT. This clinical picture could be explained by autoimmune HIT (aHIT) refractory to fondaparinux or by fondaparinux cross-reactivity, so high-dose intravenous immunoglobulin (IVIG) was given (to treat possible aHIT) and fondaparinux switched to rivaroxaban, with subsequent clinical recovery. In vitro studies revealed strong fondaparinux cross-reactivity, without aHIT antibodies. Moreover, the patient's serotonin-release assay became negative post-IVIG, suggesting in-vivo inhibition of HIT antibody-induced platelet activation. Our case illustrates fondaparinux cross-reactivity in HIT manifesting as persisting thrombocytopenia, new thrombosis, and DIC, with successful rivaroxaban treatment, adding to emerging data that oral factor Xa inhibitors are efficacious for treating HIT.